2009
DOI: 10.1007/s00467-009-1231-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and metabolic features of urolithiasis and microlithiasis in children

Abstract: We evaluated the clinical, radiological and metabolic features of 162 children with urolithiasis or microlithiasis who had been referred to our pediatric nephrology clinics between 1998 and 2008 with suspected urolithiasis. The medical histories of these children (78 girls, 84 boys), who ranged in age from 2 months to 16 years (mean age 5.59 +/- 0.35 years), were reviewed retrospectively for clinical and metabolic features of urinary tract calculi. Urinary tract infections (UTI) were present in 45.9% of the ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
98
3
43

Year Published

2011
2011
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(170 citation statements)
references
References 45 publications
26
98
3
43
Order By: Relevance
“…Previous studies of pediatric patients with urolithiasis in endemic regions have demonstrated a high rate of UTIs in patients with stones, ranging from 45.9% to 70%. [16][17][18] However, these investigations have noted varying rates of struvite stones (10%-44.8%). 16,19 Although we only have stone analysis results available on 8 patients, it is unlikely that the remainder of our patients had a significant struvite component, given the lack of staghorn calculi.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of pediatric patients with urolithiasis in endemic regions have demonstrated a high rate of UTIs in patients with stones, ranging from 45.9% to 70%. [16][17][18] However, these investigations have noted varying rates of struvite stones (10%-44.8%). 16,19 Although we only have stone analysis results available on 8 patients, it is unlikely that the remainder of our patients had a significant struvite component, given the lack of staghorn calculi.…”
Section: Discussionmentioning
confidence: 99%
“…78 RKM'ye daha çok karın ağrısı, İYE ve hematüri, dizüri gibi semptomu olan çocuklarda rastlanmaktadır; ancak hiçbir semptomun olmadığı çocuklar da olabilmektedir. 77,79 Hastalar, daha büyük renal taşı olan çocuk hastalara göre genellikle daha küçüktür (infantil dönem). 77,79 RKM'ler renal taş oluşumunun ilk basamağı olarak kabul edilmektedir ve ilerleyen yaşlarda sıklıkla renal taş oluşumu ile birliktedir.…”
Section: Nütrisyonel Nedenlerunclassified
“…77,79 Hastalar, daha büyük renal taşı olan çocuk hastalara göre genellikle daha küçüktür (infantil dönem). 77,79 RKM'ler renal taş oluşumunun ilk basamağı olarak kabul edilmektedir ve ilerleyen yaşlarda sıklıkla renal taş oluşumu ile birliktedir. 78,80 Ancak Türkiye'den bildirilen iki çalış-mada, RKM'nin %37 hastada, diğer çalışmada ise %29 hastada zaman içerisinde kendiliğinden kaybolduğu saptanmıştır.…”
Section: Nütrisyonel Nedenlerunclassified
See 1 more Smart Citation
“…It affects from 5 to 15% of the world population, and has a great impact on economy and health worldwide 1-3. In spite of the advances in surgical approaches, there have not been many changes in the history of nephrolithiasis. It affects youngsters between the third and fourth decades of life 4,5 , but it is also common in children 6 .…”
Section: Introductionmentioning
confidence: 99%